MEDIA DARING SEBAGAI SOLUSI PELAKSANAAN PENGUMUMAN KELULUSAN PADA MASA DARURAT COVID-19 - Nurkhoiriyah Nurkhoiriyah (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
This Best Practice aims to overcome the problem of implementing the announcement of the graduation of class XII during the COVID-19 emergency. Online media was chosen as the solution to the problem because it can be accessed anytime and anywhere. Before online media is used to carry out graduation announcements, it is necessary to begin by planning the layout of the announcement design, the information that will be displayed in the graduation announcement layout. The datas that will be entered into online media, among others, student numbers, exam numbers, student names, student grades and graduation status, then create a username and password that will be used by students to log into online media. Usernames and passwords that have been made are distributed to students, then paste online media on the school website. It can be concluded that online media that can be accessed anytime and anywhere is very appropriate as a solution to the announcement of graduation class XII at SMA Negeri 1 Pengasih during the COVID-19 emergency.